The Political Economy of Livestock in Early States. Issue 1 (February 2023) - Corcoran-Tadd, Noa; Price, Max; Caramanica, Ari
Abstract : Animals were central elements in many early state political economies. Yet the roles of livestock in building and financing the state generally remain under-theorized, particularly in comparison with other major elements such as crop intensification and bureaucratic technologies. We compare the political economies of two highly centralized and expansive states—the Inca in the central Andes and Ur III in southern Mesopotamia—through a deliberately animal-focused perspective that draws attention to the unique social and economic roles of the livestock that underpinned both imperial financing and household resilience. Despite important differences in the trajectories of the two case studies, attention to the roles played by animals in early states highlights several underlying dynamics of broader interest including the translation between modes of production and accumulation, the interplay between animal-based mobilities and territorial integration, and the functions of livestock in state regimes of value and political subjectivity.